P4HB recurrent missense mutation causing Cole-Carpenter syndrome. Issue 3 (20th December 2017) - Balasubramanian, Meena; Padidela, Raja; Pollitt, Rebecca C; Bishop, Nicholas J; Mughal, M Zulf; Offiah, Amaka C; Wagner, Bart E; McCaughey, Janine; Stephens, David J
Abstract : Background: Cole-Carpenter syndrome (CCS) is commonly classified as a rare Osteogenesis Imperfecta (OI) disorder. This was following the description of two unrelated patients with very similar phenotypes who were subsequently shown to have a heterozygous missense mutation in P4HB . Objectives: Here, we report a 3-year old female patient with severe OI who on exome sequencing was found to carry the same missense mutation in P4HB as reported in the original cohort. We discuss the genetic heterogeneity of CCS and underlying mechanism of P4HB in collagen production. Methods: We undertook detailed clinical, radiological and molecular phenotyping in addition, to analysis of collagen in cultured fibroblasts and electron microscopic examination in the patient reported here. Results: The clinical phenotype appears consistent in patients reported so far but interestingly, there also appears to be a definitive phenotypic clue (crumpling metadiaphyseal fractures of the long tubular bones with metaphyseal sclerosis which are findings that are uncommon in OI) to the underlying genotype ( P4HB variant). Discussion: P4HB (Prolyl 4-hydroxylase, betasubunit) encodes for PDI (Protein Disulfide isomerase) and in cells, in its tetrameric form, catalyses formation of 4-hydroxyproline in collagen. The recurrent variant in P4HB, c.1178A>G, p.Tyr393Cys, sits in the C-terminal reactive centre and is said to interfere with disulphide isomerase function of the C-terminal reactive centre. P4HB catalyses the hydroxylation of proline residues within the X-Pro-Gly repeats in the procollagen helical domain. Given the inter-dependence of extracellular matrix (ECM) components in assembly of a functional matrix, our data suggest that it is the organisation and assembly of the functional ECM that is perturbed rather than the secretion of collagen type I per se. Conclusions: We provide additional evidence of P4HB as a cause of a specific form of OI-CCS and expand on response to treatment with bisphosphonates in this rare disorder.